Prediction Model of Related Factors with Youth Fertility in Kalimantan - Kurniatin, Lydia Febri; Marsita, Elma; Irawaty, Dian Kristiani; Elfiyan, Indra (JURNAL INFO KESEHATAN, 2022)
Adolescent fertility is an essential issue because it is associated with the level of morbidity and mortality of mothers and children. Kalimantan provinces own fertility problems. Teenagers are still complex, including Age Specific Fertility Rate 15-19 years is still significant. It is recorded that 4.6% of children aged 10-17 years in Kalimantan have got married. The objective of this study is to identify the predictive model of factors correlated with provincial youth fertility in Kalimantan. The analysis was conducted by employing descriptive and inferential methods and binary logistic regression. The results of the study were among 433 adolescents in Kalimantan, 11% were married, 9.9% had given birth or were pregnant with their first child, 14.1% experienced sexual relations and 3.1% encountered sex at <15 years of age. The data employed was the 2017 Indonesian Health Demographic Survey with a unit of analysis for adolescents aged 15-19 years in 5 provinces in Kalimantan totaling 433 respondents. The sampling technique employed total sampling. Statistically, it is discovered a significant relationship between age, marital status, adolescent sexual behavior, contraceptive use status, education level, economic status, and access to the internet with youth fertility in Kalimantan. The results of logistic regression analysis displayed that the variable of family planning use possess the most effect on adolescent fertility simultaneously with the strength of the relationship OR (Expβ) = 0.2.  Suggestions for further research to further scrutinize relevant programs such as maturing age at marriage and parenting skill to suppress adolescent fertility.